2020
DOI: 10.1108/ecam-11-2019-0621
|View full text |Cite
|
Sign up to set email alerts
|

The complexities of managing historic buildings with BIM

Abstract: PurposeThe adoption of building information modelling (BIM) in managing built heritage is an exciting prospect, but one that presents complexities additional to those of modern buildings. If challenges can be identified and overcome, the adoption of historic BIM (HBIM) could offer efficiencies in how heritage buildings are managed.Design/methodology/approachUsing Durham Cathedral as a case study, we present the workflows applied to create an asset information model to improve the way this unique UNESCO World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…The role of FM in historical urban development is infrequently studied, and its contribution to sustaining the operation of heritage buildings is sometimes problematic. Most studies stated that FM was mainly related to supporting core activities within a singleowned building(s) [9,[32][33][34][35][36][37][38][39]. In fact, FM could be understood from a broader perspective [40], for example, understanding FM from urban scale viewpoints.…”
Section: Interaction Between Urban Fm and The Hul Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of FM in historical urban development is infrequently studied, and its contribution to sustaining the operation of heritage buildings is sometimes problematic. Most studies stated that FM was mainly related to supporting core activities within a singleowned building(s) [9,[32][33][34][35][36][37][38][39]. In fact, FM could be understood from a broader perspective [40], for example, understanding FM from urban scale viewpoints.…”
Section: Interaction Between Urban Fm and The Hul Approachmentioning
confidence: 99%
“…From the examined papers, this study found out that 71.05% of the literatures were from the heritage management or conservation field, while 28.95% of them were FM oriented (Figure 6). From the combined field of works of literature, it was discovered that BIM-GIS related topics were discussed the most [33,34,[36][37][38][39][54][55][56][57][58][59][60][61][62][63] and represented 21.05% of the examined papers. Only one article (1.32%) directly addressed a financial issue of urban heritage facility management [64].…”
Section: Subject Areas Of Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elghaish and Abrishami (2020a) presented an integration of several methods to support automating risk/reward sharing amongst project parties thus enhancing IPD core team members' relationship by proposing a centralised cost management system and exploiting EVM and ABC within IPD. Charlton et al (2020) suggested that the adoption of BIM in managing built heritage is an exciting prospect, but one that presents complexities additional to those of modern buildings. Qian and Papadonikolaki (2020) examined how trust is affected by the introduction of blockchain technology in construction supply chain management in shifting trust in construction supply chains through blockchain technology.…”
mentioning
confidence: 99%